Two new species of Magnolia (Magnoliaceae) from Peru - Arroyo, Frank; Serna-González, Marcela (Phytotaxa, 2020)
Two species of Magnolia from the Amazonian lowland humid forests of Peru are newly described and illustrated: M. clementinana and M. manuensis. Magnolia clementinana is similar to M. peruviana in leaf shape, but its villous indumentum on branchlets and leaves and larger flowers set it apart. Magnolia manuensis is similar to M. rimachii in habit and leaf shape but differs in its larger flowers and more numerous carpels. Information on habitat and conservation status of both species is also provided.